2003
DOI: 10.1037/1076-8998.8.4.235
|View full text |Cite
|
Sign up to set email alerts
|

Managing HIV at the workplace: An empirical study of HIV and HR managers in Singapore.

Abstract: Drawing from previous research on individual differences, AIDS, and concerns for face, the author developed and tested a model examining the predictors (knowledge of AIDS transmission, level of homophobia, and concern for face) of AIDS fear and its organizational outcomes (perceived organizational consequences of hiring people living with HIV and attitudes toward disclosure of HIV-related information at the workplace). Data were collected using mail survey. Structural equation modeling was used to examine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Stigma and discrimination in the workplace were identified as possible causes for the low rate of disclosure found in that setting [21]. Previous research has suggested that employers don’t have the appropriate knowledge about HIV, ART and its success in turning the HIV epidemic into a manageable, chronic-like disease [21], [36]. This lack of education leads to discrimination and inappropriate employment terminations [21], [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stigma and discrimination in the workplace were identified as possible causes for the low rate of disclosure found in that setting [21]. Previous research has suggested that employers don’t have the appropriate knowledge about HIV, ART and its success in turning the HIV epidemic into a manageable, chronic-like disease [21], [36]. This lack of education leads to discrimination and inappropriate employment terminations [21], [36].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has suggested that employers don’t have the appropriate knowledge about HIV, ART and its success in turning the HIV epidemic into a manageable, chronic-like disease [21], [36]. This lack of education leads to discrimination and inappropriate employment terminations [21], [36]. Employers should therefore be the target of pilot educational programs focused on disseminating knowledge of PLHIV.…”
Section: Discussionmentioning
confidence: 99%
“…Scale scores were used as indicators for each construct in the models. We accounted for the effects of measurement error by fixing the value of the unique variance indicator as one minus the reliability multiplied by the scale variance (Niehoff & Moorman 1993, Sinclair et al 2002, Lim 2003. We used the coefficient alpha as the indicator of reliability for all scales.…”
Section: Discussionmentioning
confidence: 99%
“…Scale scores were used as indicators for each construct in the models. We accounted for the effects of measurement error by fixing the value of the unique variance indicator to be one minus the reliability multiplied by the scale variance (Lim, 2003). To control for baseline levels of job satisfaction and well‐being we included time 1 measures of these variables in our model.…”
Section: Methodsmentioning
confidence: 99%